STRATEGI INOVATIF PENGELOLAAN PESERTA DIDIK: MEMBANGUN TARBIYAH ‘AQLIYAH PADA PESERTA DIDIK DI MA DARUL FALAH SUMBERGEMPOL: STRATEGI INOVATIF PENGELOLAAN PESERTA DIDIK: MEMBANGUN TARBIYAH ‘AQLIYAH PADA PESERTA DIDIK DI MA DARUL FALAH SUMBERGEMPOL - Izzatul Amalina; Agus Zaenul Fitri; Muhammad Fauzi Ridwan (JIPSKi: Jurnal Ilmu Pendidikan dan Studi Keislaman, 2024)
Abstract A strategy for developing student innovation is really needed by every educational institution in improving the quality of its students. This research aims to reveal the strategy carried out by MA Darul Falah Sumbergempol in developing tarbiyah 'aqliyah which is carried out for students with management applied in coaching as an effort to improve quality. The method used in this research is qualitative, while data analysis uses qualitative descriptive analysis. The results of data analysis show that tarbiyah 'aqliyah has a strong foundation from the Al-Qur'an and Al-Hadith as well as the views of the ulama. The implementation of 'aqliyah tarbiyah at this institution is clearly realized in the organization's mission, namely providing integral monotheism-based education that combines several tarbiyah. This mission is the embodiment of MA Darul Falah Sumbergempol's vision, namely to create a superior and competitive educational institution to produce a generation that is devout, intelligent and independent. The vision and mission are outlined in the educational objectives of MA Darul Falah Sumbergempol which aim to shape people according to their vision and mission. Keywords: Innovative Strategy, Tarbiyah Aqliyah